Kształcenie kadry hotelarskiej w szkołach średnich i wyższych w Polsce na tle wybranych krajów Europy - Piotr Dominik (Ekonomiczne Problemy Turystyki, 2017)
Analysis and the assessment of the process of educating hotel staffs on the level of the upper secondary school and the higher education are a purpose of this study. In the publication they made analysis of the system of the vocational education in Poland both on the average as well as higher level about the practical profile. Examples of system terminations were given in European countries so as Germany, England, Denmark. The best hotel training schools were also presented from behind border, among others Ecole Hoteliere de Lausanne from Switzerland. In twenty-four hours of the transformation in the vocational education it is impossible not to mention Polish Frames of Qualifications and the way in which they are functioning with reference to the European Qualifications Framework. In drawing up in detail they discussed issues concerning the programme new basis for the vocational training, including legal grounds of for her passing and functioning and correlations with the programme base of the general education.